2005
DOI: 10.1124/dmd.105.004622
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Oatp (Organic Anion-Transporting Polypeptide) Family Transporters to the Hepatic Uptake of Fexofenadine in Humans

Abstract: and 257 ؎ 84 M, respectively, suggesting that FEX could not be used as a specific inhibitor for OATP1B1 and OATP1B3, although FEX was preferentially accepted by OATP1B3. In conclusion, this is, to our knowledge, the first demonstration that OATP1B3 is thought to be a major transporter involved in hepatic uptake of FEX in humans.Several members of different uptake transporter families are thought to be involved in the hepatic uptake of substances in human liver. Since the uptake of substances from blood into he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 25 publications
6
124
0
Order By: Relevance
“…Interestingly, fexofenadine has been established to be a substrate for P-glycoprotein and several OATP transporters (OATP1A2, OATP1B3, OATP2B1) (Cvetkovic et al 1999;Nozawa et al 2004a;Shimizu et al 2005). However, one recent in vitro study reported no significant fexofenadine transport by OATP1B1 (Shimizu et al 2005). This discrepancy between in vivo and in vitro findings deserves further studies.…”
Section: Oatp1b1 Polymorphisms and Drug Disposition And Effects In Humentioning
confidence: 48%
See 1 more Smart Citation
“…Interestingly, fexofenadine has been established to be a substrate for P-glycoprotein and several OATP transporters (OATP1A2, OATP1B3, OATP2B1) (Cvetkovic et al 1999;Nozawa et al 2004a;Shimizu et al 2005). However, one recent in vitro study reported no significant fexofenadine transport by OATP1B1 (Shimizu et al 2005). This discrepancy between in vivo and in vitro findings deserves further studies.…”
Section: Oatp1b1 Polymorphisms and Drug Disposition And Effects In Humentioning
confidence: 48%
“…In a study with healthy volunteers, fexofenadine plasma concentrations were (similar to the observations with pravastatin) highest in individuals with the 521CC genotype, intermediate in the 521TC group and lowest in the 521TT group (Table 3) (Niemi et al 2005b). Interestingly, fexofenadine has been established to be a substrate for P-glycoprotein and several OATP transporters (OATP1A2, OATP1B3, OATP2B1) (Cvetkovic et al 1999;Nozawa et al 2004a;Shimizu et al 2005). However, one recent in vitro study reported no significant fexofenadine transport by OATP1B1 (Shimizu et al 2005).…”
Section: Oatp1b1 Polymorphisms and Drug Disposition And Effects In Humentioning
confidence: 98%
“…However, the relative contribution of multiple OATP isoforms to fexofenadine disposition remains controversial. Shimizu et al (Shimizu et al, 2005) have demonstrated that OATP1B3 contributes mainly to the hepatic accumulation of fexofenadine using transporter-expressing HEK293 cells. On the other hand, Niemi et al (Niemi et al, 2005) reported that the genetic polymorphism of OATP1B1 (T521C), which was been shown to decrease the transport clearance, increased the plasma AUC of fexofenadine.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that MTX is a substrate for Oatp1a4, OATP1B1, OATP1B3, and OATP1A2 (12)(13)(14). FEX is transported in vitro by Oatp1a1, -1a4, -1a5 and -1b2, and OATP1A2 (38,39), but in vitro studies of OATP1B1 and -1B3-mediated uptake of FEX are quite inconsistent (39)(40)(41). In the present study, by using Slco1a/1b -/-mice, we proved that Oatp1a/1b transporters effect a profound impact on MTX and FEX pharmacokinetics by acting as high-capacity hepatic uptake transporters that determine the overall elimination rate of these drugs.…”
Section: Figurementioning
confidence: 99%